TRIM proteins as emerging regulators of immune pathways: potential therapeutic targets in immune-related disorders - Jawed, Bilal; Kanwal, Rimsha; Zakir, Syed Khuram; Gaudio, Francesco; Esposito, Jessica Elisabetta; Ishaqui, Azfar Athar; Martinotti, Stefano; Botteghi, Matteo; Toniato, Elena (Frontiers in Immunology, 2026)
Tripartite motif (TRIM) proteins constitute a versatile family of E3 ubiquitin ligases that regulate key signaling pathways governing innate and adaptive immune responses. Their ability to modify receptor-proximal adaptors, transcription factors, and pattern recognition receptors positions them as central modulators of antiviral defense, cytokine production, and immune homeostasis. Dysregulated TRIM expression or activity contributes to the pathogenesis of autoimmune diseases, including SLE, Sjögren’s syndrome, rheumatoid arthritis, psoriasis, inflammatory bowel diseases, and type I diabetes. This review summarizes the role of TRIM proteins in innate and adaptive immunity and their signaling axis linked to autoimmune and immune-related pathologies. It also focuses on the emerging therapeutic potential, targets and clinical strategies for targeting TRIM proteins.